Parallel Gate Operations Fidelity in a Linear Array of Flip‐Flop Qubits. Issue 4 (27th January 2022) - Rei, Davide; Ferraro, Elena; De Michielis, Marco
Abstract: Quantum computers based on silicon are promising candidates for long term universal quantum computation due to the long coherence times of electron and nuclear spin states. Furthermore, the continuous progress of micro‐ and nano‐electronics, also related to the scaling of metal–oxide–semiconductor systems, makes it possible to control the displacement of single dopants thus suggesting their exploitation as qubit holders. Flip‐flop qubit is a donor based qubit where interactions between qubits are achievable for distance up to several hundred nanometers. In this work, a linear array of flip‐flop qubits is considered and the unwanted mutual qubit interactions due to the simultaneous application of two one‐qubit and two two‐qubit gates are included in the quantum gate simulations. In particular, by studying the parallel execution of couples of one‐qubit gates, namely R z ( − π 2 ) $R_z(-\frac{π }{2})$ and R x ( − π 2 ) $R_x(-\frac{π }{2})$, and of couples of two‐qubit gate, that is, i SWAP $\sqrt {\text{i}\text{SWAP}}$, a safe inter‐qubit distance is found where unwanted qubit interactions are negligible thus leading to parallel gates fidelity up to 99.9%. Abstract : The interest in semiconducting qubit for quantum computing applications prompted scientific research toward the study of scalable and robust platforms. The flip‐flop qubit, a donor‐based qubit realized implanting 31 P donor in 28 Si, is studied where the dipole–dipole interaction is exploited allowing long‐range coupling. The unwanted mutual qubit interaction, due to the simultaneous application of two one‐ and two‐qubit gates, in a linear array of qubits is investigated.